Induction of Labor with Oral Misoprostol in Nulliparous Mothers of Twins - Simões, T (2006)
The efficacy and safety of oral misoprostol for labor induction of twins is unknown. We conducted a retrospective case-control study to evaluate the use of oral misoprostol in near term (> or =35 weeks) twin pregnancies in nulliparas. Eligible cases were given 100 mcg oral misoprostol, which was repeated after 6 h if labor did not start. Either a third dose or diluted oxytocin infusion were given in intractable cases. Diluted oxytocin infusion was used for augmentation. Controls were nulliparas delivered at > or =35 weeks by elective cesarean section. The two groups were comparable in most aspects, except for fetal malpresentation, which was the major reason for avoiding induction. Of the 69 patients in whom labor was induced, 53 (76.8%) had a vaginal birth, 3 (4.3%) had a combined twin delivery, and 13 (18.8%) had a cesarean during labor. The mean length of stay of the neonates was significantly shorter among study cases, without significant difference in the frequency of delayed discharges as an overall proxy for neonatal complications. Labor induction with oral misoprostol could be offered to patients in whom near term vaginal twin delivery is unequivocally permitted and wish to deliver by the vaginal route.